Contribution to Family, Friends, School, and Community Is Associated With Fewer Depression Symptoms in Adolescents - Mediated by Self-Regulation and Academic Performance - Kurtović, Ana; Vrdoljak, Gabrijela; Hirnstein, Marina (Frontiers in Psychology, 2021)
The tendency to get involved in helping one’s family, friends, school, and community has many potential benefits such as greater compassion, concern for others, and social responsibility. Research interest in the benefits of contribution in adolescents has increased recently, but there are not many studies examining the effect of contribution on adolescents’ mental health. The present study focused on whether contribution is associated with fewer self-rated depression symptoms in adolescents. We further tested whether self-regulation and academic performance can have a mediating role in this association. A total of 423 secondary school students (233 female) from eastern Croatia participated in the study. Mean age was 16.78 (SD=1.21). Students completed measures of self-regulation, depression symptoms, and contribution (helping one’s family, friends or neighbors, mentoring peers, volunteering in one’s community, and participating in school organizations or boards), and gave information about age, gender, and academic performance. A hierarchical regression analysis revealed that contribution, self–regulation, and academic performance were related with lower levels of self-rated depression symptoms. Furthermore, mediation analysis indicated a significant indirect effect through two mediators, self-regulation and academic performance, which was stronger than a path containing only self-regulation. Academic performance alone was not a significant mediator. Our findings suggest that contribution could protect against depression by promoting self-regulation, leading to higher academic performance, and consequently fewer depression symptoms.